Educação stem em escolas públicas do Rio Grande do Sul: mapeamento das perspectivas docentes e suas implicações - Lopes, Wesllen Martins (2024)
This research is linked to the Postgraduate Program in Education (PPGE) in Research Line 1 - Training, Knowledge and Professional Development. STEM Education, an educational approach marked by the integration of the areas Science, Technology, Engineering and Mathematics in solving real problems, has been presented in the Brazilian educational context through aspects that go back to many of the expressed objectives in Basic Education curricula. As it originated in the United States of America, concerns arise about its impact on Basic Education in Brazil, especially public education, especially because it does not present a solid definition. Considering its polysemy and aspects confluent with the training curriculum, such as problem solving, technology, creativity, among others, it is up to us to reflect on whether public Basic Education teachers recognize and understand these aspects. Thus, the objective of this study is to map teachers' perspectives on the principles of STEM Education in public Basic Education in Rio Grande do Sul to identify its pedagogical, curricular, methodological and teacher training implications. To this end, we searched the literature for the bases of STEM Education, defined its principles, thematic focuses, indicators and variables. Based on the thematic focuses, in the focus groups, we investigated the familiarity of teachers with STEM potential (teachers with affinity to the principles investigated) with STEM Education. Based on the indicators, we searched the curricular documents (BNCC and RCG) for their relationships with STEM Education. With the support of the variables designed for each principle, we developed a questionnaire and investigated the conceptions of teachers working in Basic Education in RS about STEM Education. Four principles were mapped: Integration of STEM areas; Definition of each area of the acronym; Active teaching and learning mediated; and Promotion of interpersonal skills (soft skills) to students. Through triangulation of the data obtained, we discussed and mapped each principle of STEM Education. We realized that most of the aspects investigated are represented in the practices, conceptions, knowledge and understandings declared by public Basic Education teachers in a modest way. Teachers indicate STEM Education as an approach capable of promoting scientific thinking; understanding technology, its social implications and use as a tool; the student’s autonomy and active stance; interdisciplinarity; in addition to developing interpersonal skills such as creativity, problem solving, among others. STEM Education is present in the context of teachers in an incipient way, through more robust research we will be able to verify STEM Education in teacher practice and define more concrete principles for this approach in RS.